Comparative analysis of key fiber characteristics in white pima cotton (Gossypium barbadense L.): Native accessions from the Peruvian Amazon - Morales Araníbar, Luis (2024)
The fiber quality of cotton (Gossypium barbadense L.) native to the Peruvian Amazon region is one of the most versatile and essential natural fibers in the Peruvian textile industry. There is little information about the fiber quality traits of cotton genotypes native to the Peruvian Amazon region. This study investigated the fiber quality traits of Peruvian Pima cotton accessions native to the Amazon region of the La Convención Province, Cusco, Peru, to determine the lines with the greatest potential for improving fiber quality in cotton genetic breeding programs. A total of 14 cotton accessions with white fiber color, being 12 accessions of G. barbadense L. (Pima cotton) and two accessions of Gossypium sp. (unknown cotton), were analyzed. The fiber properties determined using the high volume instrument method included seven characteristics. All fiber properties were classified into five quality classes. The data on fiber quality properties were subjected to distribution, correlation, and canonical variable analysis. The results of fiber quality properties showed that the two accessions of Gossypium sp. (unknown cotton) can be promising options to be used as high-quality fiber progenies in crop genetic breeding programs or can be cultivated by regional farmers for the purpose of producing cotton with high fiber quality. Future investigations could utilize other methods of fiber quality analysis and compare the fiber quality of these cotton accessions native to the Peruvian Amazon region with other cotton species grown worldwide to improve the understanding of Pima cotton fiber quality and its applicability in different contexts of the textile industries.